2019
DOI: 10.1534/g3.119.400193
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen Using theDrosophila melanogasterTRiP RNAi Collection To Identify Metabolic Enzymes Required for Eye Development

Abstract: The metabolic enzymes that compose glycolysis, the citric acid cycle, and other pathways within central carbon metabolism have emerged as key regulators of animal development. These enzymes not only generate the energy and biosynthetic precursors required to support cell proliferation and differentiation, but also moonlight as regulators of transcription, translation, and signal transduction. Many of the genes associated with animal metabolism, however, have never been analyzed in a developmental context, thus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…We used RNAi to knock down subunits of complex I (NDUFS1) or complex V (ATPsynα) in NSCs and tumour cells with a NSC-specific driver, Worniu-GAL4 (Albertson et al, 2004). The complex I RNAi line has been validated previously (Garcia et al, 2017; Hermle et al, 2017; Owusu-Ansah et al, 2013; Pletcher et al, 2019); expression of the complex V RNAi in NSCs strongly reduced the levels of ATPsynα (Figure 1—figure supplement 2a–c). We also assessed mitochondrial morphology by stimulated emission-depletion (STED) super-resolution microscopy of mitochondria-targeted GFP (Rizzuto et al, 1995).…”
Section: Resultsmentioning
confidence: 72%
“…We used RNAi to knock down subunits of complex I (NDUFS1) or complex V (ATPsynα) in NSCs and tumour cells with a NSC-specific driver, Worniu-GAL4 (Albertson et al, 2004). The complex I RNAi line has been validated previously (Garcia et al, 2017; Hermle et al, 2017; Owusu-Ansah et al, 2013; Pletcher et al, 2019); expression of the complex V RNAi in NSCs strongly reduced the levels of ATPsynα (Figure 1—figure supplement 2a–c). We also assessed mitochondrial morphology by stimulated emission-depletion (STED) super-resolution microscopy of mitochondria-targeted GFP (Rizzuto et al, 1995).…”
Section: Resultsmentioning
confidence: 72%
“…Consistently, we found that the level of trehalose hydrolysis impacts organ size, although the observed effects are relatively mild. The tissue-specific knockdown of glycolytic genes in eyes and wing imaginal discs have been reported to have little, if any, impacts on normal morphogenesis and organ size 39,40 , suggesting that other metabolic pathways compensate for reduced glycolysis during normal development. However, reductions in glycolytic activity can attenuate JNKinduced cell death and TGFβ/Hipk-driven tissue overgrowth in imaginal discs 39,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have shown that that Nit2 has an effect on cell proliferation and may be a tumor suppressor (Lin et al 2007; Zheng et al 2015). A recent report showed that knockdown of CG8132 also strongly impaired growth and development of the Drosophila eye (Pletcher et al 2019). Further characterization of the eye and wing phenotypes in flies will further define CG8132 / Nit2 cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…In a number of different human populations, alleles of GCDH cause the metabolic disorder glutaric acidemia type I, an early-onset neurodegenerative disorder (Table 3) (Goodman et al 1995; Hedlund et al 2006; Schmiesing et al 2017; Schmiesing et al 2018). In Drosophila , expression of CG9547 is upregulated in response to starvation and oxidative stress, and its knockdown altered eye growth (Fujikawa et al 2009; Gruenewald et al 2009; Pletcher et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation